Bioorganic Phase in Natural Food: An Overview (Springer International Publishing, 2018)
The focus of this singular work is to discuss the role and importance of bioorganic phase in food products-providing the first major reference source for researchers looking to understand all aspects of the isolation, extraction and application of this major element in natural foods. From the identifying features to its applications through biotechnology and nanobiotechnology, this book covers all of the important aspects of bioorganic phase and points to future uses and methods. With chapters focusing on phase extraction and application, food product synthesis and nanoparticle application, Bioorganic Phase in Natural Food: An Overview covers both conventional and non-conventional approaches for the extraction of bioorganic phase from various food sources. Toxicity studies in nanoparticles are presented, and the vital role played by bioorganic phase toward nanoparticles synthesis is outlined in full. For any researcher looking for complete coverage of all main aspects of bioorganic phase in foods, this work provides a comprehensive and well-researched view of this important subject. .